Astrocyte Glutamate Uptake and Water Homeostasis Are Dysregulated in the Hippocampus of Multiple Sclerosis Patients With Seizures - Andrew S. Lapato; Sarah M. Thompson; Karen Parra; Seema K. Tiwari-Woodruff (ASN Neuro, 2020)
While seizure disorders are more prevalent among multiple sclerosis (MS) patients than the population overall and prognosticate earlier death & disability, their etiology remains unclear. Translational data indicate perturbed expression of astrocytic molecules contributing to homeostatic neuronal excitability, including water channels (AQP4) and synaptic glutamate transporters (EAAT2), in a mouse model of MS with seizures (MS+S). However, astrocytes in MS+S have not been examined. To assess the translational relevance of astrocyte dysfunction observed in a mouse model of MS+S, demyelinated lesion burden, astrogliosis, and astrocytic biomarkers (AQP4/EAAT2/ connexin-CX43) were evaluated by immunohistochemistry in postmortem hippocampi from MS & MS+S donors. Lesion burden was comparable in MS & MS+S cohorts, but astrogliosis was elevated in MS+S CA1 with a concomitant decrease in EAAT2 signal intensity. AQP4 signal declined in MS+S CA1 & CA3 with a loss of perivascular AQP4 in CA1. CX43 expression was increased in CA3. Together, these data suggest that hippocampal astrocytes from MS+S patients display regional differences in expression of molecules associated with glutamate buffering and water homeostasis that could exacerbate neuronal hyperexcitability. Importantly, mislocalization of CA1 perivascular AQP4 seen in MS+S is analogous to epileptic hippocampi without a history of MS, suggesting convergent pathophysiology. Furthermore, as neuropathology was concentrated in MS+S CA1, future study is warranted to determine the pathophysiology driving regional differences in glial function in the context of seizures during demyelinating disease.